2021
DOI: 10.1186/s12888-021-03057-w
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and medical staff’s experience of adolescents with suicide-related behaviors admitted to a general hospital in China: qualitative study

Abstract: Background Currently, there is increasing awareness of suicide-related behaviors. Mental health services are a key location for assisting people with suicide-related behaviors. However, few studies focused on the evaluation and experience of the mental health care system from families and the medical staff’s perspective in China. The study aims to explore parents’ and the front-line medical staff’s experience of an adolescent with suicide-related behaviors admitted to the psychiatry department … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Participants desired a greater breadth and depth of caregiverhospital communication. 32 Caregivers in the present study described similar challenges, but across settings. They indicated how internal breakdowns in communication between institutions made the reentry process difficult for their adolescents with regard to academic and social-emotional accommodations.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Participants desired a greater breadth and depth of caregiverhospital communication. 32 Caregivers in the present study described similar challenges, but across settings. They indicated how internal breakdowns in communication between institutions made the reentry process difficult for their adolescents with regard to academic and social-emotional accommodations.…”
Section: Discussionmentioning
confidence: 54%
“…Caregivers felt that hospital providers were too busy to provide detailed information regarding their children's statuses. Participants desired a greater breadth and depth of caregiver‐hospital communication 32 . Caregivers in the present study described similar challenges, but across settings.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Across EDs, GPs and inpatient units, staff were described as uninterested and dismissive of physical and psychosocial distress (Ejneborn Looi, Engström, & Sävenstedt, 2015; Hagen, Knizek, & Hjelmeland, 2018; Lindkvist et al, 2021; Mughal, Dikomitis, Babatunde, & Chew-Graham, 2021; Xanthopoulou et al, 2022). Three studies set in clinical services reported experiences of staff prioritising cases that they perceived as more ‘serious’ and patients whose injuries were not self-inflicted, further demonstrating professional discrimination (Ejneborn Looi et al, 2015; Fu et al, 2021; Hagen et al, 2018). Minimisation also resulted in care being withheld; patients were told that pain medication and medical treatments were unnecessary, with staff making comments about a ‘waste’ of beds and resources (Byrne et al, 2021; Hagen et al, 2018; Quinlivan et al, 2021).…”
Section: Resultsmentioning
confidence: 99%